2017
DOI: 10.1038/s41598-017-07861-x
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Differences in Responsiveness to Sildenafil and Tamsulosin are due to Myogenic Smooth Muscle Tone in the Human Prostate

Abstract: Lower urinary tract symptoms (LUTS) due to Benign Prostatic Hyperplasia (BPH) are highly prevalent in older men, having a profound impact on patient quality of life. Current therapeutics for BPH/LUTS target neurogenic smooth muscle tone, but response is unpredictable and many patients fail to respond. Spontaneous myogenic tone is another component of smooth muscle contractility that is uncharacterized in human prostate. To better understand and improve the predictability of patient response, we defined myogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Growth of the transitional zone underlies BPH, but also occurs throughout life ( Pradidarcheep et al, 2011 ; Timms and Hofkamp, 2011 ). However, patterns of contractility and smooth muscle tone differ between the three prostate zones and change with age ( Lee et al, 2017 ; Chakrabarty et al, 2019 ). Consequently, our findings can not be necessarily extrapolated to the central or peripheral zones and do not cover all age groups, what may represent putative limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of the transitional zone underlies BPH, but also occurs throughout life ( Pradidarcheep et al, 2011 ; Timms and Hofkamp, 2011 ). However, patterns of contractility and smooth muscle tone differ between the three prostate zones and change with age ( Lee et al, 2017 ; Chakrabarty et al, 2019 ). Consequently, our findings can not be necessarily extrapolated to the central or peripheral zones and do not cover all age groups, what may represent putative limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Using perinatal exposure to a persistent environmental contaminant (TCDD) as a model for exposure to a range of common environmental contaminants that activate the AHR, we find that the intrauterine and early postnatal environment shapes prostate noradrenergic axon density, leading to lasting changes in prostate smooth muscle response and voiding function that persist into adulthood. It is unclear why prostate baseline tension, smooth muscle activity and responsiveness to α-adrenergic receptor blockers varies so considerably among human males with LUTD ( Lee et al, 2017 ). We posit that maternal chemical exposures during fetal urogenital development may underlie this variability, creating a susceptible phenotype that sensitizes males to voiding dysfunction with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the frequency of myogenic contractions are significantly upregulated in men with clinically diagnosed BPH 17 , and hypothesised that changes to inherent myogenic contractility are driven by intrinsic factors within the prostate, notably oxytocin levels. The presence of the OXTR in the human prostate was previously described 9 and confirmed in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Organ bath studies. Tension recordings were obtained from transition zone (TZ) specimens as previously described 17 .…”
mentioning
confidence: 99%